Evaluation of monotonic tensile properties of Napier single fibre - Luqman, R. M. (2022)
Natural fibres are derived from plants and animals, and they are the most efficient replacement for synthetic fibre. However, these fibres differ widely in physicochemical characteristics, hollow of lumen, uniformity, and degree of crystallinity, resulting in inconsistent mechanical property values. In this study, the tensile properties of a single Napier fibre were investigated according to ASTMD 3822-07. The test was performed using universal testing machines at a crosshead displacement rate of 1 mm/min. It revealed that the average tensile strength and modulus of a single Napier fibre were 23.47 MPa and 0.18 GPa, respectively. The Weibull modulus was determined to be 1.4261 with a Weibull parameter estimation error of 48%.